Recovery of the Peptidoglycan Turnover Product Released by the Autolysin Atl in Staphylococcus aureus Involves the Phosphotransferase System Transporter MurP and the Novel 6-phospho-N-acetylmuramidase MupG - Kluj, Robert Maria; Ebner, Patrick; Adamek, Martina; Ziemert, Nadine; Mayer, Christoph; Borisova, Marina (Frontiers in Microbiology, 2018)
The peptidoglycan of the bacterial cell wall undergoes a permanent turnover during cell growth and differentiation. In the Gram-positive pathogen Staphylococcus aureus, the major peptidoglycan hydrolase Atl is required for accurate cell division, daughter cell separation and autolysis. Atl is a bifunctional N-acetylmuramoyl-L-alanine amidase/endo--N-acetylglucosaminidase that releases peptides and the disaccharide N-acetylmuramic acid--1,4-N-acetylglucosamine (MurNAc-GlcNAc) from the peptidoglycan. Here we revealed the recycling pathway of the cell wall turnover product MurNAc-GlcNAc in S. aureus. The latter disaccharide is internalized and concomitantly phosphorylated by the phosphotransferase system (PTS) transporter MurP, which had been implicated previously in the uptake and phosphorylation of MurNAc. Since MurP mutant cells accumulate MurNAc-GlcNAc and not MurNAc in the culture medium during growth, the disaccharide represents the physiological substrate of the PTS transporter. We further identified and characterized a novel 6-phospho-N-acetylmuramidase, named MupG, which intracellularly hydrolyses MurNAc 6-phosphate-GlcNAc, the product of MurP-uptake and phosphorylation, yielding MurNAc 6-phosphate and GlcNAc. MupG is the first characterized representative of a novel family of glycosidases containing domain of unknown function 871 (DUF871). The corresponding gene mupG (SAUSA300_0192) of S. aureus strain USA300 is the first gene within a putative operon that also includes genes encoding the MurNAc 6-phosphate etherase MurQ, MurP, and the putative transcriptional regulator MurR. Using mass spectrometry, we observed cytoplasmic accumulation of MurNAc 6-phosphate-GlcNAc in ΔmupG and ΔmupGmurQ markerless non-polar deletion mutants, but not in the wild type or in the complemented ΔmupG strain. MurNAc 6-phosphate-GlcNAc levels in the mutants increased during stationary phase, in accordance with previous observations regarding peptidoglycan recycling in S. aureus.